World Class University: Quality Parameter Higher Education in the Era Revolusi Industri 4.0 and Society 5.0 - Rochmawati, Rochmawati (Universitas Negeri Malang, 2023)
Abstract: The purpose of this research to describe World Class University (WCU) as a parameter of the quality of higher education that is able to be integrated in the management system in universities. This research uses mixing methods design with Concurrent Embedded Qualitative domination techniques. Aspects of the syntax sequence are carried out simultaneously. Data analysis is done through two stages, the first is individual case data analysis and the second is cross-case data analysis. The validity is checked with credibility, reliability, dependability, and confirmability. Results, WCU based on criteria AREI: (1) Academic, (2) Research, (3) Employability, and (4) International. WCU has an effective strategy in synergizing the era of digitally system contribution in building a quality culture and responding to global developments. In this study, quality emphasis on zero-defect must be realized and supported by commitment, competence, synergist, collaboration, actualization, and strategy as the key in universities' work towards WCU. Keywords: World Class University, Quality Parameters, Higher Education, Industrial Revolution Era 4.0, Society 5.0